Recurrent Tracheoinnominate Artery Fistula due to Stent Graft Fracture - Hyo Yeong Ahn; Bong Soo Son; Do Hyung Kim (European Journal of Pediatric Surgery Reports, 2015)
Abstract Tracheoinnominate artery fistula (TIF) is one of the most dangerous complications after tracheostomy, and fetal even after surgical repair. Recently, endovascular stent has been introduced as an option for the treatment of TIF. Unfortunately, endovascular stent repair could not replace the surgery due to rare clinical reports about the long-term follow-up and complications of stent graft. More collection of clinical data are necessary for the evaluation of long-term results. We report a rare case of recurrent TIF due to stent graft fracture after endovascular stent graft insertion in the treatment of TIF, and reviewed the world literature.